Cell-Based Protein Stabilization Assays for the Detection of Interactions between Small-Molecule Inhibitors and BRD4. (February 2015) - Schulze, Jessica; Moosmayer, Dieter; Weiske, Joerg; Fernández-Montalván, Amaury; Herbst, Christopher; Jung, Marie; Haendler, Bernard; Bader, Benjamin
Bromodomain protein 4 (BRD4), a member of the bromodomain and extra-terminal (BET) protein family, acts as a central element in transcriptional elongation and plays essential roles in cell proliferation. Inhibition of BRD4 binding to acetylated histone tails via its two bromodomains, BD1 and BD2, with small-molecule inhibitors has been shown to be a valid strategy to prevent cancer growth. We have evaluated and established two novel assays that quantify the interaction of transfected BRD4 BD1 with chemical inhibitors inside cultured cells. Both methods are based on the principle of ligand-induced protein stabilization by which the binding of a small-molecule inhibitor stabilizes intracellular BRD4 BD1 and protects it from proteolytic degradation. We demonstrate the universal character of this principle by using two orthogonal, highly sensitive detection technologies for the quantification of BRD4 BD1 levels in cellular lysates: enzyme fragment complementation and time-resolved fluorescence resonance energy transfer (TR-FRET). Upon optimization of both assays to a miniaturized high-throughput format, the methods were validated by testing a set of small-molecule BET inhibitors and comparing the results with those from a cell-free binding assay and a biophysical thermal shift assay. In addition, point mutations were introduced into BRD4 BD1, and the corresponding mutants were characterized in the TR-FRET stabilization assay.